"Cloud chasers" and "substitutes": e‐cigarettes, vaping subcultures and vaper identities. Issue 5 (24th January 2019) - Tokle, Rikke; Pedersen, Willy
Abstract: The use of e‐cigarettes is increasing, a practice denoted as vaping . We explore user motives, self‐identity as vapers and involvement in vaping subcultures, drawing on sociological theory of stigma, subcultures and symbolic boundaries. Based on analyses of semi‐structured interviews with 30 Norwegian vapers, we find that there is a vaping subculture in Norway. We identify two dominant vaper identities. The first is labelled cloud chasers . These were dedicated vapers who identified with symbols and values in the subculture. Many were politically engaged in improving vaping regulation regimes and felt a sense of belonging to a vaping community. The second group is labelled substitutes . These were former daily smokers who used e‐cigarettes for smoking cessation in a more pragmatic and defensive manner, to avoid health risks, to escape the stigma of smoking and to manage nicotine addiction. In this group, self‐identity as a vaper was generally lacking. Vaping was often symbolically linked to the stigmatised smoker identity they wanted to escape, and was restricted to private contexts. The perceived symbolic meaning of e‐cigarettes varies: for some, they are a symbol of pleasure and community. For others, they connote the stigmatised status of the addicted smoker seeking an alternative to cigarettes.